2000
DOI: 10.1021/jp9939221
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Modulation of Color and Transmittance in Chiral Nematic Liquid Crystal Containing an Azobenzene as a Photosensitive Chromophore

Abstract: All-optical switching of selectively reflected colors based on isomerization of an azobenzene (Azo) and subsequent change in transmittance was investigated in cholesteric liquid crystals (LCs) which reflect light in the visible region. Photoirradiation at 366 nm, which causes an efficient trans-cis isomerization of Azo, led to change in color of cholesteric LCs toward shorter wavelengths with a concomitant lowering of phase transition temperature from a cholesteric to an isotropic phase (T Ch-I ). Reversible c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(59 citation statements)
references
References 43 publications
1
54
0
Order By: Relevance
“…Then the optical switching of selectively refl ective colors was investigated based on photoinduced change in the helical pitch of CLCs doped with a chiral AZ. [ 45 ] Doping of cyanobiphenyl nematic LCs with chiral dopants possessing strong HTP produced CLC phases with refl ection bands in a visible region. Photoirradiation of the CLCs containing the chiral AZ resulted in a change in the helical pitch due to trans-cis isomerization of the chiral AZ, followed by the change in the refl ective wavelength.…”
Section: Phototuning Of Cholesteric Lcs (Clcs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Then the optical switching of selectively refl ective colors was investigated based on photoinduced change in the helical pitch of CLCs doped with a chiral AZ. [ 45 ] Doping of cyanobiphenyl nematic LCs with chiral dopants possessing strong HTP produced CLC phases with refl ection bands in a visible region. Photoirradiation of the CLCs containing the chiral AZ resulted in a change in the helical pitch due to trans-cis isomerization of the chiral AZ, followed by the change in the refl ective wavelength.…”
Section: Phototuning Of Cholesteric Lcs (Clcs)mentioning
confidence: 99%
“…Photoirradiation of the CLCs containing the chiral AZ resulted in a change in the helical pitch due to trans-cis isomerization of the chiral AZ, followed by the change in the refl ective wavelength. [ 45 ] Such a change in the helical pitch can be interpreted in terms of the change in the phase transition temperature caused by changing the molecular shape of the guest AZs (Figure 2 C). Recently, a series of dicholecteric ester oligomers was developed, which can fi x the cholesteric color by immobilizing the molecular ordering in a glassy state and shows applicable to optics materials with a static function.…”
Section: Phototuning Of Cholesteric Lcs (Clcs)mentioning
confidence: 99%
“…Taking into account that the molecular shape for cis isomers of 3,3 -disubstituted azobenzenes (rod-like) and 4,4 -disubstituted azobenzenes (bent) is different, these results strongly support the theory that the pitch changes are related to the order parameter affected by the photoisomerization of azobenzene molecules. The multiple dopants system may also contain photoresponsive chiral dopants and non-photoresponsive codopants [32,82,96,97,[105][106][107][108][109][110]. In these systems, the pitch lengths are determined by the HTPs of both dopants, and the photoresponsive dopant has the additional function of photosensitization.…”
Section: Multiple Dopantsmentioning
confidence: 99%
“…[3,4] The sensitivity of ChLCs to external parameters, such as temperature, the presence of impurities, and light, has led to many practical applications and has been the subject of much theoretical research. [2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Several mechanisms have been proposed to explain the role that the dopant molecules play in the modulation of the macroscopic chirality of ChLCs. [11,[24][25][26][27][28] Recently, we reported that the mechanism of the helical-pitch shift that is induced by achiral dopants (as well as in dimesogenic compounds) is due to enhancement of smectic A (SmA)-like clusters in the cholesteric phases.…”
Section: Introductionmentioning
confidence: 99%